21st century Hollywood : movies in the era of transformation - Dixon, Wheeler W., 1950- (Rutgers University Press, 2011)
21st-Century Hollywood introduces readers to the global transformations of today's movies and describes the decisive roles that Hollywood is playing in determining the digital future for world cinema. It offers clear, concise explanations of a major paradigm shift that continues to reshape our relationship to the moving image. Filled with numerous detailed examples, the book will both educate and entertain film students and movie fans alike.